Effectiveness of Tempe Yogurt and Tempe Juice on Pregnancy Hypertension - Endah Yulianingsih; Sri Sujawatty; Yollanda Dwi Santi Violentina; Herman Priyono Luawo (EMBRIO: Jurnal Kebidanan, 2024)
Data from the Global World Health Organization shows that hypertension is currently a global concern. Hypertension is caused by cardiovascular disease, and all of them cause death. According to report, only 54 percent of adults with hypertension were diagnosed, 42 percent received treatment, and only 21 percent had treatable hypertension. This needs to be underlined that efforts to increase awareness and management of hypertension are required. One of the non-communicable diseases that causes most deaths is hypertension. Based on the performance report of the South City Community Health Center, there were relatively high cases of hypertension in pregnant women in the last six months, namely 10 cases. Age, genetic factors, and parity can cause hypertension in pregnant women. This study aims to determine the effectiveness of tempeh yogurt and tempeh spice juice against hypertension in pregnancy in the South City Health Center Working Area. A quantitative study with a quasi-experimental two-group pretest-posttest design was conducted from April to September 2023. Samples were taken using purposive sampling of 40 samples, where the samples were divided into two intervention groups, namely 20 respondents who were given intervention using tempe yogurt three times a day, 200 ml, and 20 respondents were given 200 ml of tempeh spice yogurt three times a day. The results of the analysis showed that respondents aged more than 35 years (45 percent) in group A and aged 20-35 years (40 percent) in group B. Parity less than 2- more than 4 (65 percent) in group A, parity 2-4 in group B. There was no history of hereditary hypertension (85 percent) in group A and (80 percent) in group B. There was a significant difference before and after the tempeh yogurt and tempeh spice juice intervention on systolic and diastolic blood pressure (p less than 0.05). There was a significant difference in the reduction in systolic blood pressure after being given tempeh yogurt and tempeh spice juice (p less than 0.05). It can be concluded that one effort to reduce pregnancy hypertension is by consuming tempeh yogurt and tempeh spice juice regularly.